Pilot study of over-the-counter drugs applied among the pediatric population in Bulgaria - Valentina Petkova; Bozhidarka Radoslavova Hadzhieva (Pensoft Publishers, 2021)
Herbal medicines have evolved through their traditional use in a specific or cultural context. The pharmacological effects of herbal medicines are not due to their "natural" origin, but to the complex character of biologically active substances. Pediatricians have begun to integrate the use of complementary / alternative medical therapies with conventional health care. The first aim of the study was to make an analysis of over-the-counter (OTC) drugs (OTCDs) with a plant component. The secondary aim was to investigate OTCDs in terms of composition and nosology for use by the pediatric population in Bulgaria. Registered OTC drugs with a herbal component for children are prescribed for the treatment of colds, pain, gastrointestinal diseases, mild sleep disorders, neurovegetative dystonias and kinetosis, urinary tract inflammation, liver disease, and are also applied topically to inflammation, trauma, urticaria and scars.